1982
DOI: 10.1097/00000658-198205000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Operations on the Electrical Activity of the Human Stomach Recorded During the Postoperative Recovery Period

Abstract: This study attempts to characterize any changes occurring in the human gastric control electrical rhythm (CER), following a variety of gastric surgical procedures. Pairs of electrodes were implanted in selected specific sites on the stomachs of 57 patients undergoing either antrectomy and vagotomy, proximal gastric vagotomy (PGV), vagotomy and drainage, gastric resection without vagotomy, or fundoplication. Five patients undergoing nongastric operations served as controls. After operation recordings were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…30,89 Irregular antral activity was reported following truncal and complete gastric vagotomy by Hegglin et al 45 and Wilbur and Kelly 85 however this was not observed in any studies of highly selective vagotomy. 30,84,85,88,89 Tachygastria has been reported relatively consistently following vagotomy, 84,[89][90][91] and bradygastria was observed by Bortolotti et al, 88 supporting the known role the vagus has on influencing ICC rate and rhythm. 92 Fundoplication is associated with high rates of vagal injury.…”
Section: Effect Of Vagotomymentioning
confidence: 95%
See 1 more Smart Citation
“…30,89 Irregular antral activity was reported following truncal and complete gastric vagotomy by Hegglin et al 45 and Wilbur and Kelly 85 however this was not observed in any studies of highly selective vagotomy. 30,84,85,88,89 Tachygastria has been reported relatively consistently following vagotomy, 84,[89][90][91] and bradygastria was observed by Bortolotti et al, 88 supporting the known role the vagus has on influencing ICC rate and rhythm. 92 Fundoplication is associated with high rates of vagal injury.…”
Section: Effect Of Vagotomymentioning
confidence: 95%
“…A variety of post-vagotomy slow wave abnormalities have been described, 45,84,85,88 and a smaller number of studies report no convincing alteration to gastric electrical activity with vagotomy. 30,89 Irregular antral activity was reported following truncal and complete gastric vagotomy by Hegglin et al 45 and Wilbur and Kelly 85 however this was not observed in any studies of highly selective vagotomy. 30,84,85,88,89 Tachygastria has been reported relatively consistently following vagotomy, 84,89-91 and bradygastria was observed by Bortolotti et al, 88 supporting the known role the vagus has on influencing ICC rate and rhythm.…”
Section: Effect Of Vagotomymentioning
confidence: 97%
“…The vagus nerve plays an important role in regulating ICC frequency, 28 and stable high gastric frequencies have been variably demonstrated after vagotomy. 29,30 The persistent high frequency phenotype observed in our symptomatic group is plausibly a manifestation of vagal dysfunction. Vagal nerve pathology in diabetic gastropathy was first postulated in the earliest observations of diabetic gastroparesis by Kassander, 31 and vagal nerve 14 abnormalities such as reduced myelinated fiber density have been demonstrated in humans, albeit inconsistently.…”
Section: Discussionmentioning
confidence: 78%
“…The vagus nerve is important in regulating ICC frequency, 31 with stable high gastric frequencies demonstrated after vagotomy in previous studies. 32,33 In addition, abnormally high gastric frequency has also recently been observed in patients with longstanding type 1 diabetes and peripheral neuropathy, likely on the basis of co-existent autonomic neuropathy. 16 Therefore, high frequency gastric activity appears to be a general indicator of vagal nerve dysfunction or injury, although its sensitivity as a biomarker for this pathology requires further research.…”
Section: Discussionmentioning
confidence: 98%